Two Adapted Techniques in Studies of DNA Fingerprinting of Septoria tritici Populations - Cordo, Cristina Alicia (2006)
In this study two new protocols with nonradioactive techniques applied on DNA analysis with RFLP (Restriction Fragment Length Polymorphism) were presented. They have been modified from the DIG (Boehringer Mannheim) and Photogene 2.0 (Life Technology) Systems. DNA probes were random-primed labeled with the specific compounds for each system. The quantity of digested DNA, the concentrations of the probe in the hybridization step and the concentration of the anti-body conjugate for the detection process were optimized. The improvements from the original protocol for the DIG System were an increase in the concentration of the labeled probe in the hybridization step and in the concentration of the anti-digoxigenin-AP conjugate in the detection process. There were no quantitative changes in the protocol of the Photogene System, but the quality of the washing process was improved for the post hybridization, blocking and detection steps. There is an economic advantage when using the Photogene System if the cost for reaction is analyzed. A brief comment about the frequency of the RFLP patterns from the isolates of both geographical sampled regions was also presented. The following advantages were found when these systems were used: safety in handling, no decay of labeled probes, reusable hybridization mixes (in the case of the DIG System), extremely short exposure times in the signal detection and economical differences in the cost per reaction for the Latin American economical conditions. This procedure saved time and cut costs without reducing sensitivity.